A study protocol for a randomised open-label clinical trial of artesunate-mefloquine versus chloroquine in patients with non-severe Plasmodium knowlesi malaria in Sabah, Malaysia (ACT KNOW trial) - Grigg, M J (BMJ Publishing Group, 2014)
INTRODUCTION: Malaria due to Plasmodium knowlesi is reported throughout South-East Asia, and is the commonest cause of it in Malaysia. P. knowlesi replicates every 24 h and can cause severe disease and death. Current 2010 WHO Malaria Treatment Guidelines have no recommendations for the optimal treatment of non-severe knowlesi malaria. Artemisinin-combination therapies (ACT) and chloroquine have each been successfully used to treat knowlesi malaria; however, the rapidity of parasite clearance has not been prospectively compared. Malaysia's national policy for malaria pre-elimination involves mandatory hospital admission for confirmed malaria cases with discharge only after two negative blood films; use of a more rapidly acting antimalarial agent would have health cost benefits. P. knowlesi is commonly microscopically misreported as P. malariae, P. falciparum or P. vivax, with a high proportion of the latter two species being chloroquine-resistant in Malaysia. A unified ACT-treatment protocol would provide effective blood stage malaria treatment for all Plasmodium species. METHODS AND ANALYSIS: ACT KNOW, the first randomised controlled trial ever performed in knowlesi malaria, is a two-arm open-label trial with enrolments over a 2-year period at three district sites in Sabah, powered to show a difference in proportion of patients negative for malaria by microscopy at 24 h between treatment arms (clinicaltrials.gov #NCT01708876). Enrolments started in December 2012, with completion expected by September 2014. A total sample size of 228 is required to give 90% power (α 0.05) to determine the primary end point using intention-to-treat analysis. Secondary end points include parasite clearance time, rates of recurrent infection/treatment failure to day 42, gametocyte carriage throughout follow-up and rates of anaemia at day 28, as determined by survival analysis. ETHICS AND DISSEMINATION: This study has been approved by relevant institutional ethics committees in Malaysia and Australia. Results will be disseminated to inform knowlesi malaria treatment policy in this region through peer-reviewed publications and academic presentations. TRIAL REGISTRATION NUMBER: NCT01708876.